The Soviet Scene : A Geographical Perspective - Bater, James H. (London Edward Arnold, 1989)
This book is a concise introduction to the complexities of the Soviet system, focusing on issues of general concern. It looks at the processes of decision-making, the continuities and changes between Imperial and Soviet Russia, and the divergences between ideals and reality in the Soviet Union.
Include Maps, Graphs and Index
Keywords: Soviet Union -- Soviet Union -- Economic conditions -- 1975-1985.